DISPUTE RESOLUTION IN THE SOUTH AFRICAN SOCIAL SECURITY SYSTEM: THE NEED FOR MORE APPROPRIATE APPROACHES - MAT Nyenti (Obiter, 2021)
The right to social security in South Africa is adjudicated and enforced mainly by means of litigation. This article examines litigation as a mechanism for the resolution of social security disputes in South Africa and its impact on both the right to have access to court and to social security. It argues that court-based adjudication may not be the most appropriate means of adjudicating social security claims. This is particularly as South Africa is a country where social security beneficiaries have limited knowledge of the laws and procedures, coupled with a lack of publicly-provided legal assistance/representation for social security cases. Dispute resolution mainly through the courts may contribute to the limitation of their right to seek redress and by implication, their right to have access to social security. Finally, the article proposes the investigation of more appropriate dispute-resolution processes. This is due to the failure of court-based adjudication to ensure access to justice (and to social security); constitutional requirements arising from the protection of the rights of access to justice and to social security; the Constitution’s focus on protecting persons who are particularly vulnerable and desperate; the availability of other (more appropriate) dispute-resolution mechanisms; and the relatively successful implementation of these mechanisms in the resolution of social security disputes in comparative jurisdictions.